Islamic arts decoration as an attraction at the exterior of the mosque - Mazlan, Ahmad Aiman; Zakariya, Khalilah (2016)
This study examined how the Islamic Art decoration at the mosque exterior contributes in attracting people. What this paper discusses the Islamic Arts as it was in the past which was the art utilized for the sake of glorifying the Almighty God. It also addresses the prevalent issue on the scarcity of using the Islamic Arts on the mosque exterior. Thus, the first phase of the study involved a reading on the Islamic Arts. Then, the next phase proceed to identify the people’s perceptions by interviewing the experts. Lastly is the evaluation of the existing Islamic Art on the site study. Through the study, the research highlights the importance of the Islamic Art decoration on mosque exterior as an attraction for people.